2012
DOI: 10.1002/aur.236
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Porphyrin Metabolism: A Potential Biological Marker for Autism Risk Assessment

Abstract: Autism (AUT) is a complex neurodevelopmental disorder that, together with Asperger Syndrome and Pervasive Developmental Disorder-Not Otherwise Specified (PDD-NOS), comprises the expanded classification of autistic spectrum disorder (ASD). The heterogeneity of ASD underlies the need to identify biomarkers or clinical features that can be employed to identify meaningful subtypes of ASD, define specific etiologies, and inform intervention and treatment options. Previous studies have shown that disordered porphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Numerous independent studies have found that children with ASDs have significantly elevated levels of urinary porphyrins, which are indicative of greater symptom severity (Geier & Geier, 2006Austin & Shandley, 2008;Geier et al, 2009;Kern et al, 2010Kern et al, , 2011Youn et al, 2010). Although measuring porphyrin levels might not be a valid diagnostic tool for ASDs on its own (Shandley et al, 2014), it may help identify a subgroup of subjects with ASDs (Heyer et al, 2012).…”
Section: Air Pollution and Heavy Metalsmentioning
confidence: 99%
“…Numerous independent studies have found that children with ASDs have significantly elevated levels of urinary porphyrins, which are indicative of greater symptom severity (Geier & Geier, 2006Austin & Shandley, 2008;Geier et al, 2009;Kern et al, 2010Kern et al, , 2011Youn et al, 2010). Although measuring porphyrin levels might not be a valid diagnostic tool for ASDs on its own (Shandley et al, 2014), it may help identify a subgroup of subjects with ASDs (Heyer et al, 2012).…”
Section: Air Pollution and Heavy Metalsmentioning
confidence: 99%
“…50 However, a role for haem in neuronal development and function has been well documented and some reports have linked the risk of a subgroup of autism patients with disturbances of porphyrin metabolism. 51,52 AIP is also associated with an elevated risk of developing hepatocellular cancer. 53 Thus, variants in the haem enzyme genes HMBS, CPOX and PPOX with molecular phenotypic consequences can be considered as genetic predisposing factors for adverse effects of some drugs and hormones in susceptible patients.…”
Section: Triggering Agents For Porphyriasmentioning
confidence: 99%
“…Heyer et al [113] investigated the urine levels of pentapophyrin and coproporphyrin as potential markers for ASD risk by comparing a group of 30 male children with autistic disorder, 14 with PDD-NOS, and 32 neurotypical controls. ASD children (including PDD-NOS and autism) had higher urinary levels of pentaporphyrin and coproporphyrin compared to age matched controls.…”
Section: Other Types Of Biomarkersmentioning
confidence: 99%